Increased respiratory morbidity associated with exposure to a mature volcanic plume from a large Icelandic fissure eruption. - Carlsen, Hanne Krage; Ilyinskaya, Evgenia; Baxter, Peter J; Schmidt, Anja; Thorsteinsson, Throstur; Pfeffer, Melissa Anne; Barsotti, Sara; Dominici, Francesca; Finnbjornsdottir, Ragnhildur Gudrun; Jóhannsson, Thorsteinn; Aspelund, Thor; Gislason, Thorarinn; et al. (Springer Science and Business Media LLC, 2021)
The 2014-15 Holuhraun eruption in Iceland was the largest fissure eruption in over 200 years, emitting prodigious amounts of gas and particulate matter into the troposphere. Reykjavík, the capital area of Iceland (250 km from eruption site) was exposed to air pollution events from advection of (i) a relatively young and chemically primitive volcanic plume with a high sulphur dioxide gas (SO2) to sulphate PM (SO42-) ratio, and (ii) an older and chemically mature volcanic plume with a low SO2/SO42- ratio. Whereas the advection and air pollution caused by the primitive plume were successfully forecast and forewarned in public advisories, the mature plume was not. Here, we show that exposure to the mature plume is associated with an increase in register-measured health care utilisation for respiratory disease by 23% (95% CI 19.7-27.4%) and for asthma medication dispensing by 19.3% (95% CI 9.6-29.1%). Absence of public advisories is associated with increases in visits to primary care medical doctors and to the hospital emergency department. We recommend that operational response to volcanic air pollution considers both primitive and mature types of plumes.